Transcriptional regulation of the salmonella enterica std fimbriaoperon by the RcsCDB system - Farizano, Juan Vicente (2019)
In Salmonella enterica serovar Typhimurium, the RcsCDB regulatory system controls the expression of genes involved in synthesis of colanic acid, formation of flagella and virulence. Here, we show that activation of the RcsCDB system downregulates expression of std, an operon that encodes fimbriae involved in Salmonella attachment to the mucus layer in the large intestine. Bioinformatic analysis predicts the existence of an RcsB-binding site located 180 bp upstream to the +1 transcription start site of the std promoter, and electrophoretic mobility shift assays confirm that RcsB binds the std promoter region in vitro. This study adds RcsB to the list of regulators of std transcription and provides an example of modulation of fimbriae synthesis by a signal transduction system.